CONCENTRATION OF HEAVY METALS IN THE SOIL AND PLANTS AROUND WASTE DUMPSITES IN ENUGU METROPOLIS, NIGERIA - M. N. Okeke; Paul Chukwuka Eze; C. N. Eze (Universitas Trisakti, 2019)
Aims: The purpose of this project is to find the concentration of heavy metals in the topsoil and the plant around the waste dumpsite from Enugu municipal solid disposal sites. Methodology and Results: There was a collection of soil samples from four designated public municipal solid waste dumpsites in Enugu metropolis. The soil samples were collected at 10m intervals from the centre location point of each dumpsite at a constant depth. The sample collection design include centre (0 m) of the dumpsites, 10, 20, and 30m. However, the control sample was 65m away from the centre of dumpsites at the same depth. Plant samples were taken just at the centre (0m), and control measures were at 65m distance away from each dumpsite. The Goat grasses harvested were taken to the lab to determine and analyse heavy metals intake from the soil. These samples were analysed using atomic absorption spectrophotometer (AA320N) model. On the average, high concentrations of Zn, Fe, Mn, Cu, and Pb found in the soil samples collected at the centre of the dumpsites were 141.70, 121.5, 75.53, 70.33 and 64.53 mg/kg respectively. The results were statistically analysed and had significant effects between the samples (p < 0.05). Conclusion, significance, and impact study: The heavy metals studied were within the acceptable or permissible limit by WHO and FAO. However, the plant intake of zinc at Presidential that was beyond the maximum permissible level of 163.45 mg/kg Zn compared with FAO and WHO standard of 50 mg/kg.